A Study on Crack Depth Measurement in Steel Structures Using Image-Based Intensity Differences - Ju-Yeong Jung; Hyuk-Jin Yoon; Hyun-Woo Cho (Advances in Civil Engineering)
This paper seeks to propose an image-based noncontact testing method in crack depth measurement. To this end, it predicted the crack depth using the intensity values of cracks and verified its validity. To analyze the intensity values of cracks, eight stainless steel specimens with an increase in crack depths ranging from 0 to 17.5 mm at an average of 2.5 mm were fabricated, and a contrast index was attached to the center of the crack of the specimens painted with black matte spray for accurate analysis. Through various experiments, it was found that the intensity values of the cracks which decrease with the depth of the cracks were inductively formulated, and the average error was about 15% when the crack depth predicted by the empirical equation was compared with the actual crack depth. In addition, the validation of the intensity reduction equation obtained by the inductive method was verified, and it was confirmed that the crack depth can be predicted by the intensity value of the crack.